Free Radical Scavenging Activity of Ethanol Extract and Fraction of Water Hyacinth Stem (Eichhornia Crassipes (Mart.) Solms) Using DPPH Method - Zulfa Nurmawadah; Willy Tirza Eden (Universitas Negeri Semarang, 2024)
Background: Water hyacinth has been shown to have radical scavenging activity as an antioxidant. Some secondary metabolites contained in water hyacinth have antioxidant activity. Aim: This study aims to identifying the antioxidant activity of ethanol extracts, fractions, and isolates of water hyacinth stems. Material and Methods: The extraction of water hyacinth stem with maceration using 96% ethanol solvent. The antioxidant activity test of the extract, fraction, and isolate was carried out through , DPPH (1,1-Diphenyl-2-picrylhydrazyl) methods to determine the IC50 values. Phytochemical screening to determine the compounds contained in the isolation. The active fraction was then made into an isolate FTIR and GC-MS to determine the compounds. Results: Phytochemical screening test on isolate B8 is suspected to be positive for terpenoid or monoterpenoid compounds, The functional groups of isolate active ethanol extract of water hyacinth stem (Eichhornia crassipes (Mart.) Solms) consist of functional groups C-H, C-H aliphatic, CH3, C-O, C=C aromatic, Carboxylic acid stretch, Methylene CH bend, tert-butyl.